A Comprehensive Review on Phytochemistry and Pharmacology of Homoeopathic Medicine Rhus Toxicodendron - Goswami, Abanti; Saka, Vara Prasad; GV, Narasimha Kumar; Biswas, Bibaswan (Homœopathic Links, 2022)
Background Rhus toxicodendron is a homoeopathic medicine introduced into the homoeopathic system by Hahnemann in 1816, and ever since, it has been used to relieve arthritis, rheumatism and skin disorders.Aim This review aimed to search the literature for the phytochemical and pharmacological investigations of homeopathic medicine Rhus tox. The assembled data of Rhus tox could be beneficial in helping researchers concentrate on the most pivotal aspects that still need to be examined.Discussion In the Homoeopathic Pharmacopoeia of India, Toxicodendron pubescens P. Mill (Atlantic poison oak) and Toxicodendron radicans (poison ivy) have been mentioned as synonyms of Rhus toxicodendron Linn. The allergic contact dermatitis caused by touching the leaves of the Toxicodendron plants is believed to give the plant its specific name. Available literature illustrated the medicinal and pharmacological potential against various inflammatory diseases, including arthritis, showing immunomodulatory and anti-neoplastic activity.Conclusion There is a need to establish evidence for the activities mentioned in the literature. The detailed knowledge regarding the mechanism of Rhus toxicodendron Linn. would help the scientific community understand the field of homeopathic medicine more closely.
Keywords: Rhus toxicodendron Linn.; anti-arthritic activity; immunomodulatory activity; homoeopathic medicine